THE EVOLUTION OF ENGLISH LANGUAGE LEARNING: INTRODUCTION TO ONLINE PLATFORMS - Зюбан, В.В. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
This article discusses the process of using online platforms in English lessons. As well as the advantages of using Internet resources to increase the motivation and involvement of students in the educational process. The list of digital resources that can be used at different levels of education by foreign language teachers is analyzed.
Keywords: English; updated system; technology; online platforms; motivation